2023
DOI: 10.3389/fpsyt.2022.1067437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and effects of sleep-disordered breathing on middle-aged patients with sedative-free generalized anxiety disorder: A prospective case-control study

Abstract: ObjectiveGeneralized anxiety disorder (GAD) and sleep-disordered breathing (SDB) share similar symptoms, such as poor sleep quality, irritability, and poor concentration during daily activities. This study aims to investigate the proportion of undiagnosed SDB and its impacts on anxiety severity and autonomic function in newly diagnosed, sedative-free GAD patients.MethodsThis prospective case-control study included newly diagnosed GAD patients and control participants with matched age, sex, and body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Intermittent hypoxia triggers anxiety behaviors in mice ( 126 ). In men, OSA has been linked to increased severity of anxiety ( 127 ). OSA is more likely in men aged 18 to 64 years with anxiety and hypertension than those with only hypertension ( 128 ).…”
Section: Pathophysiology and Associations Of Osa With Other Disordersmentioning
confidence: 99%
“…Intermittent hypoxia triggers anxiety behaviors in mice ( 126 ). In men, OSA has been linked to increased severity of anxiety ( 127 ). OSA is more likely in men aged 18 to 64 years with anxiety and hypertension than those with only hypertension ( 128 ).…”
Section: Pathophysiology and Associations Of Osa With Other Disordersmentioning
confidence: 99%
“…Therefore, FeCO levels may vary in patients with SDB. Some studies have shown that FeCO levels may be valuable in assessing SDB [16][17] . The repeated hypoventilation and hypoxia events during sleep in patients with SDB may lead to oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%